A Critical Examination of the Current Paradigms on the Origin of Writing in Mesopotamia (Enki & Ptah. Journal of Technology and Trade in Ancient Egypt and Western Asia, 2025)
This article explores the methodological and historiographical challenges that persist in examining the complex topic of the origins of writing in antiquity, with focus on the earliest writing systems from Southwestern Asia and Northern Africa (proto-cuneiform, proto-hieroglyphic, and proto-Elamite). A review of scholarly literature reveals a lack of consensus regarding who invented writing first and when. This disagreement seems to stem from ideological factors, as scholars in different fields often advocate for the region they specialize in as the birthplace of writing. This situation is ultimately rooted in the prestige associated with writing in modern societies, which has led to historical narratives that overemphasize the role of this technology as a marker of civilization in antiquity. This study aims to highlight this phenomenon and lay the groundwork for a more nuanced paradigm that fully considers the interconnected cultural, technological, and social factors of the late 4th millennium BCE.